Pioneer Bluffs & The Rogler Legacy - Marva Weigelt (Symphony in the Flint Hills, 2010)
What goal would provide you with sufficient motivation to travel several hundred miles into unknown territory on foot, without the luxury of well-marked roads or motels and restaurants at predictable intervals along the way?
Keywords: Pioneer Bluffs; territory; immigrants; European; Kansas Territory; Charles Rogler; Henry Brandley; antislavery; proslavery; People of the South Wind; Chase County; Asch; Bazaar; Cottonwood River; Starving Kansas; Land of Famine; drought; Kansas State Agricultural College; Maud Sauble; family; farm; K-State; Flint Hills Scenic Byway; Matfield Green; Mary Satchell Rogler